2007
DOI: 10.1080/00016340701644991
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial growth factor +936 C/T polymorphism is associated with an increased risk of endometriosis in a Japanese population

Abstract: The VEGF +936 T allele is associated with an increased risk of stage III-IV endometriosis in a Japanese population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
2
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 20 publications
5
44
2
4
Order By: Relevance
“…Bhanoori et al (44) demonstrated that the -460T/+405C haplotype of VEGF was less frequently identified in females with endometriosis compared to the controls, and VEGF -460 T/T homozygotes and the T allele are associated with a higher risk of endometriosis in Chinese females. There are also studies that demonstrate the association of the VEGF +936 C/T polymorphism in Caucasian and Japanese females with endometriosis (45,46). In addition, several meta-analyses have demonstrated that the VEGF +936 C/T SNP can predispose to endometriosis (47)(48)(49).…”
Section: Discussionmentioning
confidence: 99%
“…Bhanoori et al (44) demonstrated that the -460T/+405C haplotype of VEGF was less frequently identified in females with endometriosis compared to the controls, and VEGF -460 T/T homozygotes and the T allele are associated with a higher risk of endometriosis in Chinese females. There are also studies that demonstrate the association of the VEGF +936 C/T polymorphism in Caucasian and Japanese females with endometriosis (45,46). In addition, several meta-analyses have demonstrated that the VEGF +936 C/T SNP can predispose to endometriosis (47)(48)(49).…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7][9][10][11][12][13][14] The general characteristics of included eligible studies in the meta-analysis are presented in Table 1. Among the enrolled literatures, there were three studies of Asians decent 3,5,9 and eight studies of Caucasians decent.…”
Section: General Characteristics Of Eligible Studiesmentioning
confidence: 99%
“…[3][4][5][6][7][9][10][11][12][13][14] The general characteristics of included eligible studies in the meta-analysis are presented in Table 1. Among the enrolled literatures, there were three studies of Asians decent 3,5,9 and eight studies of Caucasians decent. 4,6,7,[10][11][12][13][14] These subjects were carried out in Korean, Japanese, Indian, Spanish, Turkish, Austrians, Italians, and Iranians.…”
Section: General Characteristics Of Eligible Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the public National Center for Biotechnology Information Single Nucleotide Polymorphism database and available literature, we selected six VEGF candidate polymorphisms, ie, −1498T.C (rs833061) and −1154G.A (rs1570360) in the promoter region, −634C.G (rs2010963) and −7C.T (rs25648) in the 5' UTR, and 936C.T (rs3025039) and 1612G.A (rs10434) in the 3' UTR. Each polymorphism showed a minor allele frequency of at least 0.10 in the Japanese population, 23,[32][33][34][35] and all polymorphisms were investigated in terms of their association with various types of diseases or clinical situations. 22,[36][37][38][39] The six VEGF genotypes were evaluated using TaqMan R minor groove binding probe-based polymerase chain reaction, and confirmed by direct sequencing, as described previously.…”
Section: Vegf Genotypingmentioning
confidence: 99%